PENGARUH MODEL PEMBELAJARAN TEMATIK BERBASIS WEBBED BERBASIS TEKNOLOGI MEDIA TERHADAP MATA PELAJARAN IPS UNTUK HASIL BELAJAR SISWA TEMA MAKANAN SEHAT KELAS V - Didi Syahrir; Firman; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Social studies learning is a life lesson that can be used for social science ideas to help citizens learn with methods that can be used in their daily lives. Foreground reality is the main culprit, because the students in the class are young children who still view the world as a whole, their learning still relies on real objects and their personal experiences. The second reason is that children's holistic thinking skills will be underdeveloped due to the application of separate subject-based learning in elementary schools. The early and upper classes were feuding, which was a third factor. In addition, teachers often emphasize certain concepts or learning methods. The purpose of this study is to assess efficiency. Social studies learning for fifth grade students at SDN 15 Patamuan using a thematic educational model of the webbed media technology type with mobility assistance, as well as for elementary school students in grade five Negeri 15 Patamuan. Using a similar model but without using the media. Class V of SD Negeri 15 Patamuan which was taught with examples of thematic learning of the Webbed type with help from class V and motion media technology at SDN 02 Patamuan without the help of technology utilizing motion media was able to compare the various social studies learning standards. This study uses a quantitative storytelling methodology. Using the Webbed-type integrated learning model can more effectively and efficiently advance student learning in accordance with integrated learning objectives, according to research conducted by fifth grade students at SDN 15 Patamuan. A teacher continues to play a role in the teaching and learning process from the perspective of content preparation, presentation, and student training.